Engineering Flexible, Self-Supported Si@CNF Nanofiber Membrane for High-Performance Li-Ion Battery Anode - Wang, Wendan; Liu, Yi; Li, Ruolan; Wu, Weiying; Yang, Zhihao; Huang, Tieqi; Chen, Limiao; Liu, Hongtao (Industrial & engineering chemistry research, 2025)
Silicon-based materials are promising alternatives to graphite anodes in lithium-ion batteries (LIBs) due to their ultrahigh theoretical capacity (4200 mAh g– 1). However, severe volume expansion and particle detachment during cycling hinder their practical application. Herein, a flexible, self-supported core–shell Si@CNF nanofiber membrane is engineered via a scalable electrospinning-carbonization strategy. The unique architecture features silicon nanoparticles encapsulated within a conductive carbon nanofiber network, effectively buffering volume changes and enhancing structural integrity. Electrochemical evaluations reveal that the optimized Si@CNF-2 anode delivers a high initial discharge capacity of 1460.2 mAh g– 1 at 0.2 A g– 1, with 86.4% capacity retention after 500 cycles. Remarkable rate capability is demonstrated with capacities of 1052.7 and 814.4 mAh g– 1 at 0.5 and 1 A g– 1, respectively. The superior performance is attributed to the synergistic effects of the 3D carbon scaffold, the binder-free design, and pseudocapacitive contributions (91% at 0.9 mV s– 1). This work provides a scalable approach to fabricating high-energy-density anodes for next-generation flexible LIBs. The flexible self-supported core–shell Si@CNF nanofiber membrane, engineered via a scalable electrospinning-carbonization strategy, serves as a promising anode material for lithium-ion batteries.